Keaktifan dan kreativitas mahasiswa PGMI dalam Mengembangkan Media Pembelajaran yang menarik Di UIN maulana malik ibrahim malang - Ainiy, Kuniy Anisata (Maliki Interdisciplinary Journal, 2025)
Education plays an important role in shaping the personality and abilities of the younger generation. In this article, we will discuss how students of the Elementary Madrasah Teacher Education Study Program (PGMI) are active and creative in developing innovative learning media. The study conducted a literature study and case study method on students of the education study program. by looking at relevant literature. The results of the analysis show that learning tools created using new technology can increase students’ interests and desires. Internal and external factors play an important role in supporting student activity, while creativity is the key to success in creating effective learning. Activity-based learning and information technology are relevant approaches to improving the quality of learning and students’ readiness as professional